La Vitamina D Nei Pazienti Con Malattia Renale Cronica. Issue 2 (April 2015) - Cozzolino, Mario; Elli, Francesca; Cappelletti, Laura; Ciceri, Paola
Vitamin D in CKD Important mineral homeostasis disorders occur from the early stages of chronic kidney disease (CKD), despite patients may be completely asymptomatic. These disorders, affecting the serum levels of calcium, phosphorus, parathyroid hormone, and vitamin D, have a striking impact on the patient's prognosis as they affect the cardiovascular system. The new term "Chronic Kidney Disease-Mineral Bone Disease" (CKD-MBD) was created to define bone disease during CKD as a systemic disorder tightly linked to cardiovascular calcifications and disabilities. Vitamin D deficiency has a main role in the pathogenesis of CKD-MBD through the pleiotropic actions of this hormone. Vitamin D receptors (VDRs) are ubiquitarious, and their activation has shown protective effects against the development of secondary hyperparathyroidism as well as anti-hypertensive, anti-inflammatory, anti-fibrotic, immunomodulating, anti-proliferative, anti-diabetic, and anti-proteinuric properties. These mechanisms can explain, at least in part, the influence of vitamin D status for avoiding and delaying cardiovascular disease and CKD progression. These findings strongly support the importance of an early diagnosis of mineral homeostasis disorders in CKD and the need for a correction of vitamin D deficiency to prevent the disabilities and major events related to it.